The impact of reciprocal training on developing the specific endurance abilities of junior handball players - Jaloub, Asst.Prof.Dr.Haider Abdul Wahid; Saleh, Asst.Prof.Dr.Samer Mahdi Mohammed; Abdullah, Bahar Osman (Sulaimani Journal for Humanities, 2026)
The importance of this research lies in its aim to elevate the skills of junior handball players by enhancing their endurance capabilities. This, in turn, contributes to increased and sustained speed in both offensive and defensive skills through the use of appropriate and specialized exercises employing the reciprocal training method. The research problem stems from the fact that the researchers, being coaches in specialized handball centers, observed that the defining characteristic of modern handball is its emphasis on speed, which is essential for meeting the game's demands. This is achieved through training at a fast and intense pace until the final whistle. Therefore, those involved in the field sought to find the best training methods and techniques to develop endurance and specific abilities, thereby maximizing the adaptation of these abilities and their impact on key handball skills. Consequently, the researchers decided to begin this study by utilizing exercises that effectively enhance endurance through reciprocal training for junior handball players. The study aimed to develop reciprocal training exercises for junior handball players. Then, the study aimed to identify the effect of reciprocal training on developing specific endurance capabilities (speed endurance, strength endurance, and performance endurance) in junior handball players. Research Methodology and Field Procedures: The researchers used the experimental method due to its suitability to the nature of the problem. The research sample consisted of junior players from Al-Kufa Club for the 2023/2024 sports season, totaling (16) players. They were then randomly divided into two groups (experimental and control) using simple random methods (drawing lots), with (6) players in each group. Based on the research results, the following conclusions were reached: - The reciprocal training method contributed positively to developing the specific endurance capabilities of junior handball players. Furthermore, increasing the number of repetitions and varying the performance in the reciprocal training method, in addition to adjusting the training loads appropriately for the sample, led to an improvement in the specific endurance capabilities of the junior handball players.
Keywords: Reciprocal style and special endurance skills; junior handball